Pengaruh Usia Menarche Dengan Kejadian Menapause Pada Perempuan Di Pengajian Al-Hidayah Kabupaten Gresik - Munisah, Munisah (IJMT : Indonesian Journal of Midwifery Today, 2023)
Introduction: There are three stages in a woman's life, namely menarche, reproduction, and menopause. Menarche is the first menstrual experience experienced by a woman. This stage indicates that the female reproductive system is in normal condition. While menopause is a condition where a woman does not experience menstruation anymore. This is due to a decrease in estrogen production by the ovaries of 300 mg per day to zero. Menopause experienced by women is closely related to the period of menarche, the sooner menarche comes the slower menopause comes. Methods: This study used an analytic correlation design with a cross sectional approach. The population of the study was women who were members of the Al-Hidayah recitation of Gresik district, totaling 30 respondents who met the inclusion criteria. The instrument used is Google Form which is distributed to respondents. Bivariate analysis of data with statistical tests using the Rank Spearman test with a significance value of ɑ= 0.05. From the results that have been tested using rank Spearman, the result is p value = 0.539 > 0.05, then Ho is accepted, which can be concluded that there is no relationship between the age of menarche and the incidence of menopause. Conclutions: Based on the results of this study, it is adjacent to the existing theory, namely the earlier the menarche, the later the onset of menopause, but the results of this study state that there is no relationship. Although the results of the study do not state that there is no relationship between the age of menarche and the incidence of menopause, it is our hope that all women who are about to enter menopause will prepare themselves both physically and psychologically.